Functional Analysis of the “Green Revolution” Gene Photoperiod-1 and Its Selection Trends During Bread Wheat Breeding - Wu, Yongzhen; Liu, Jiahui; Hu, Guimei; Xue, Huixian; Xu, Huiyuan; Zhao, Chunhua; Qin, Ran; Cui, Fa; Sun, Han (Frontiers in Plant Science, 2021)
Flowering is central to the transformation of plants from vegetative growth to reproductive growth. The circadian clock system enables plants to sense the changes in the external environment and to modify the growth and development process at an appropriate time. Photoperiod-1 (Ppd-1), which is controlled by the output signal of the circadian clock, has played an important role in the wheat ‘Green Revolution’. In the current study, we systematically studied the relationship between Ppd-1 haplotypes and both wheat yield- and quality-related traits, using genome-wide association analysis and transgenic strategies, and found that highly appropriate haplotypes had been selected in the wheat breeding programs. Genome-wide association analysis showed that Ppd-1 is associated with signiﬁcant differences in yield-related traits in wheat, including spike length, heading date, plant height and thousand-grain weight. Ppd-1-Hapl-A1 showed increased spike length by 4.72%–5.93%, whereas Ppd-1-Hapl-B1 and -D1 displayed earlier heading date by 0.58%–0.75% and 1.24%–2.93%, respectively, decreased plant height by 5.64%–13.08% and 13.62%–27.30%, respectively and increased thousand-grain weight by 4.89%–10.94% and 11.12%–21.45%, respectively. Furthermore, the constitutive expression of the Ppd-D1 gene in rice significantly delayed heading date and resulted in reduced plant height, thousand-grain weight, grain width and total protein content. With reference to 40 years of data from Chinese wheat breeding, it was found that the appropriate haplotypes Ppd-1-Hapl-A1, -B1 and -D1 had all been subjected to directional selection, and that their distribution frequencies had increased from 26.09%, 60.00% and 52.00% in landraces to 42.55%, 93.62% and 96.23% in wheat cultivars developed in the 2010s. A Ppd-B1 methylation molecular marker was also developed to assist molecular wheat breeding. This research is of significance for fully exploring the function of the Ppd-1 gene and its genetic resource diversity, to effectively use the most appropriate haplotypes and to improve crop yield and sustainability.